Unbiased Sampling for Rodents and Other Small Mammals: How to Overcome Neophobia Through Use of an Electronic-Triggered Live Trap—A Preliminary Test - Stryjek, Rafal; Kalinowski, Artur; Parsons, Michael H. (Frontiers in Ecology and Evolution, 2019)
Live-trapping of urban rodents and other small mammals poses several challenges for researchers and pest control professionals (PMPs). Most traps are novel to the natural environment and elicit neophobic, or trap-shy, behaviors. Thus, animals captured in traditional traps may either be the least risk averse, or most-desperate. Consequently, individuals of the lowest social ranks, those in poorest health, and the slowest learners are more likely to be captured. This is problematic for research because non-random samples may lead to over-generalization and false conclusions. To address these problems, we developed an inconspicuous, hanging live-trap prototype. In addition to being hard to detect, the trap enables setting several parameters of animal movement and detection before the trap is triggered. The neophobic reaction could then be significantly reduced because animals do not need to enter any trap-like objects – instead they move and feed on a familiar surface. At a time predefined by the user, the triggering mechanism drops a transparent cover over the animal, preventing it from fleeing and enabling transport to the laboratory, mark-and-release or disposal. Here, we report our initial purpose, design and preliminary results. Animals triggered the trap 34 times during our one-month preliminary assessment. During this time, 32 individuals were captured (25 Norway rats and 7 house mice), for a 94% catch rate. Video surveillance revealed no obvious signs of non-random sampling – all trapped rats were representative of a broad range of sizes and ages. There were no signs of low social status (e.g. scar markings, parasitism, or poor health). Importantly, we found a low latency following capture, as the released animals showed no instances of increased exploratory or cautious behaviors, such as rearing or sniffing near the hidden traps. More monitoring of this design is needed before future conclusions can be drawn, however, these results should encourage a full range of experimental trials from neuroscientists, urban ecologists, pest control professionals (PMPs) and conservationists who seek randomized samples or who work with trap-shy species.